Structural and optical properties of RF-sputtered CdTe thin films grown on CdS:O/CdS bilayers - Das N.K.; Farhad S.F.U.; Chakaraborty J.; Gupta A.K.S.; Dey M.; Al-Mamun M.; Matin M.A.; Amin N. (International Journal of Renewable Energy Research, 2023)
Cadmium sulfide; Cadmium telluride; Crystallite size; Energy gap; Glass substrates; II-VI semiconductors; Light transmission; Magnetron sputtering; Optical constants; Optical films; Optical properties; Argon ambient; Bi-layer; Different substrates; Polycrystalline; R.F. magnetron sputtering; RF sputtering; Structural and optical properties; Substrates temperature; Thin-films; XRD spectra; Thin films